The Revealing the Practice of the Merdeka Belajar Curriculum: Implementation in Elementary Schools - Rahmadani, Widya Laila; Mustika, Dea (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study explores the implementation of the independent learning curriculum in elementary schools, focusing on SDN 118 Pekanbaru. Employing a qualitative approach, the research follows a descriptive method to elucidate the implementation of the Merdeka Curriculum. The process encompasses planning, execution, and conclusion stages. During planning, teachers analyze the Education Unit's characteristics, develop the Operational Curriculum, and create teaching modules like Projek Penguatan Profil Pelajar Pancasila. Implementation involves initial, core, and concluding activities. The teacher establishes a positive classroom environment through friendly greetings, checks attendance, and gauges students' readiness. Core activities entail a collaborative understanding of learning objectives, aligning them with the subject matter, offering alternative activities based on student's interests, and fostering engagement through practical tasks. The teacher assesses learning outcomes in the concluding phase through exercises, attendance, responses, homework, and Q&A sessions. Various assessment methods are employed, including practice questions, summaries, and group discussions. The teacher inspires students through engaging activities, challenges misconceptions, and provides positive feedback. Recognition is given to bold and correct answers, while guidance is provided for students requiring further support in understanding the material.